2020
DOI: 10.1200/jco.2020.38.15_suppl.9001
|View full text |Cite
|
Sign up to set email alerts
|

KEYNOTE-604: Pembrolizumab (pembro) or placebo plus etoposide and platinum (EP) as first-line therapy for extensive-stage (ES) small-cell lung cancer (SCLC).

Abstract: 9001 Background: Pembro monotherapy showed durable antitumor activity as third-line or later therapy for metastatic SCLC, leading to FDA approval in that setting. KEYNOTE-604 was a double-blind, phase 3 study of pembro + EP vs placebo + EP as first-line therapy for ES-SCLC (NCT03066778). Methods: Eligible patients (pts) with previously untreated ES-SCLC and no untreated CNS metastases were randomized 1:1 to pembro 200 mg Q3W or saline placebo for up to 35 cycles plus 4 cycles of standard-dose EP. Pts with CR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 0 publications
1
27
0
2
Order By: Relevance
“…Patients with asymptomatic brain metastases were allowed to enroll. Le et al reported the primary efficacy, safety, and biomarker results of the VISION trial [9].…”
Section: The Vision Trial: Tepotinibmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients with asymptomatic brain metastases were allowed to enroll. Le et al reported the primary efficacy, safety, and biomarker results of the VISION trial [9].…”
Section: The Vision Trial: Tepotinibmentioning
confidence: 99%
“…The co-inhibitory receptor TIGIT is expressed on multiple immune cells and inhibits T cells as well as NK cells by binding to its ligand on tumor and antigenpresenting cells [8][9][10]. It was hypothesized that anti-TIGIT antibodies preventing this binding reaction might restore the anti-tumor response and complement the activity of anti-PD-(L)1 antibodies.…”
Section: Anti-tigit Antibody Tiragolumabmentioning
confidence: 99%
See 3 more Smart Citations